Analisis Kinerja Operasional Light Rail Transit (LRT) Stasiun Demang Kota Palembang - Sari, Nadra Mutiara; Aszharri, Arief; Anggraini, Nita; Praditya, Norca (Jurnal Talenta Sipil, 2024)
This research examines the operational performance and user satisfaction of the Light Rail Transit (LRT) mass transportation system in Palembang City, particularly on the LRT Demang Lebar Daun station corridor. The study involves the collection of primary and secondary data, including passenger numbers, waiting times, travel intervals, and travel times. The research results indicate that the average number of passengers per LRT station is approximately 10 passengers, resulting in a load factor ranging from 9% to 11%. While passenger comfort levels are relatively high, this low ridership may impact operational efficiency. The waiting times and travel intervals of the LRT are relatively short, enhancing passenger comfort, but warrant operational considerations. Furthermore, the study notes that the round-trip travel time on the LRT is approximately 2 hours, 33 minutes, and 57 seconds. However, limited parking facilities at the Demang Lebar Daun station can affect the interest in using the LRT. In order to improve operational performance and user satisfaction of the LRT, this research recommends an evaluation of travel intervals, waiting times, and daily LRT trip numbers. Additionally, improvements in parking facilities at LRT stations should be considered to enhance the convenience of using this mode of transportation.